Tulisan Bak Mobil Truk sebagai Mobile Linguistic Landscape: Analisis Linguistik dan Ideologi Vernakular - Muhammad Ashar Kadir; Djuanda Djuanda; Mantasiah Mantasiah (Badan Pengembangan dan Pembinaan Bahasa, 2026)
This study examines the linguistic landscape phenomenon in writings found on truck beds in Indonesia as a form of linguistic practice in mobile public spaces. Writings on truck beds are understood as vernacular discourse that represents life experiences, social identity, religious values, social criticism, and the ideology of marginalised communities, particularly truck driver communities. This study uses a qualitative descriptive approach with visual observation and semiotic analysis of the sentences written on truck beds. The data are analysed through theme classification, discourse function, and symbolic meaning within the framework of linguistic landscape and sociolinguistic theory. The results show that truck bed writing functions not only as a medium of personal expression, but also as a means of social communication, moral control, and symbolic criticism that moves across geographical and social spaces. This research contributes theoretically by expanding the study of linguistic landscape to the realm of non-institutional and mobile public spaces, and empirically by providing systematic documentation of the vernacular language practices of the working class. Practically, the findings of this study are relevant to the development of context-based critical literacy, the study of popular culture, and the formulation of language policies that are more inclusive of the language practices of marginalised communities. Abstrak Penelitian ini mengkaji fenomena mobile linguistic landscape pada tulisan bak mobil truk di Indonesia sebagai bentuk praktik kebahasaan vernakular di ruang publik bergerak. Berbeda dengan kajian linguistic landscape konvensional yang memusatkan perhatian pada ruang statis, penelitian ini memosisikan bak truk sebagai medium linguistik yang melintasi batas geografis dan sosial secara dinamis. Melalui analisis terhadap tiga belas data tulisan bak truk, penelitian ini mengidentifikasi empat tema dominan, yaitu wacana religius dan spiritualitas jalanan, refleksi emosional dan pengalaman hidup, humor dan kritik sosial, serta wacana relasional dan gender. Analisis linguistik difokuskan pada fitur leksikal, strategi retoris (metafora konseptual, aforisme, paralelisme, paradoks), fungsi pragmatik, dan makna ideologis. Temuan menunjukkan bahwa tulisan bak truk merupakan bottom-up sign yang berfungsi sebagai counter-discourse terhadap wacana dominan serta merepresentasikan suara autentik masyarakat kelas pekerja. Penelitian ini berkontribusi pada perluasan konseptual kajian linguistic landscape menuju ruang publik bergerak (mobile public space) dan memperkuat relevansi kajian wacana vernakular dalam sosiolinguistik Indonesia.